No longer radical : understand mastectomies and choose the breast cancer care that's right for you - Teal, Christy; Brem, Rachel (Simon Element, 2023)
"A life-saving and empowering guide to understanding breast cancer detection, prevention, and treatment options, from two top doctors in the field-Rachel Brem, a breast radiologist, and Christy Teal, a breast surgeon-who have also made the personal decisions to have mastectomies"--